Optimizing Prompt Engineering for Generative AI - HERMAN, Erik (Mercury Learning & Information, 2025)
In the constantly changing field of artificial intelligence, effective communication and prompt engineering have become essential for developers, researchers, and tech enthusiasts to guide and improve AI.